2021
DOI: 10.1017/jog.2021.48
|View full text |Cite
|
Sign up to set email alerts
|

Fluid resonance in elastic-walled englacial transport networks

Abstract: Englacial water transport is an integral part of the glacial hydrologic system, yet the geometry of englacial structures remains largely unknown. In this study, we explore the excitation of fluid resonance by small amplitude waves as a probe of englacial geometry. We model a hydraulic network consisting of one or more tabular cracks that intersect a cylindrical conduit, subject to oscillatory wave motion initiated at the water surface. Resulting resonant frequencies and quality factors are diagnostic of fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In this case, the drastic change in VLP periods over the early part of the eruption likely represents an evolving conduit geometry due to some combination of a widening upper conduit and a change in conduit length due to a changing dip angle and reservoir attachment depth. A shallow dike/sill above the main Halema'uma'u reservoir could have also impacted the resonance (54); this would potentially be consistent with some seismic inversions (21,33), but such additional source complexity is not needed according to other seismic and geodetic inversions (7,9,11).…”
Section: An Evolving Magma Plumbing System Geometrymentioning
confidence: 79%
“…In this case, the drastic change in VLP periods over the early part of the eruption likely represents an evolving conduit geometry due to some combination of a widening upper conduit and a change in conduit length due to a changing dip angle and reservoir attachment depth. A shallow dike/sill above the main Halema'uma'u reservoir could have also impacted the resonance (54); this would potentially be consistent with some seismic inversions (21,33), but such additional source complexity is not needed according to other seismic and geodetic inversions (7,9,11).…”
Section: An Evolving Magma Plumbing System Geometrymentioning
confidence: 79%
“…First, moulin cross-sectional area, and thus water storage capacity, can vary substantially over the course of a day or season (Figs. 6c and 9b), and features such as englacial crevasses and reservoirs may be present (e.g., McQuillan and Karlstrom, 2021). Second, in instances where moulins are reactivated over multiple melt seasons (Chu, 2014;Smith et al, 2017), there may be substantial deformation, as suggested by cable breakage in boreholes (Ryser et al, 2014;Wright et al, 2016).…”
Section: Comparison Of Modeled and Observed Moulin Geometriesmentioning
confidence: 99%
“…Crack waves (and their induced tube waves in wellbores) are used for diagnosing the fracture geometries in unconventional hydrocarbon reservoirs (Henry et al., 2002; Liang et al., 2017; Lipovsky & Dunham, 2015; Tary et al., 2014). The resonating or humming signals in glaciers have also been attributed to crack waves (Gräff et al., 2019; McQuillan & Karlstrom, 2021; Métaxian et al., 2003; Stuart et al., 2005). Natural cracks in the subsurface are complex in shape and usually form an inter‐connected network.…”
Section: Introductionmentioning
confidence: 99%